Correlation Between Health Belief Model on Early Mobilization Behavior during the Postpartum Period in Jember Regency - Aini, Nurul; Sulistiyawati, Ika (Window of Health : Jurnal Kesehatan, 2023)
Maternal mortality is still a major public health problem. Every day, about 810 women around the world die cause of related to pregnancy, childbirth, and puerperium. Jember Regency has the highest number of maternal deaths in East Java in 2021, namely 115 deaths, of which 61 (53%) occurred during the puerperium. This study aims to determine the relationship between the health belief model and early mobilization behavior during the postpartum period in the Jember District. The health belief model consists of perceived susceptibility, perceived severity, perceived benefits, and perceived barriers. Research with a cross-sectional design was conducted on 123 postpartum mothers in the Jember Regency. A multistage random sampling technique was used to sample the population. Data were collected through questionnaires and observation checklists of mobilization behavior, then analyzed using descriptive data analysis and the Spearman correlation test. The results of the descriptive data analysis showed that 86.2% of postpartum mothers were aged 20-35 years, and 40.7% had a high school level of education. In comparison, the results of the Spearman correlation test showed perceived susceptibility (p=0.000, ρ = 0.346), perceived severity (p=0.001, ρ = 0.309), perceived benefits (p=0.000, ρ = 0.450) and perceived barriers (p=0.000, ρ = -0.428). It can be concluded that perceptions of susceptibility, severity, and benefits have a positive relationship with early mobilization behavior, while perceived barriers have a negative relationship. It is necessary to strengthen community and family empowerment efforts by increasing the role of cadres and families in providing motivation and support to postpartum mothers to carry out early mobilization to prevent complications during the postpartum period and to accelerate recovery in postpartum mothers after giving birth.